(untitled) (Eurasian Journal of Ecology, 2020)
The impact of pesticides and persistent organic pollutants (POPs) on biota is a serious problem for many countries. Currently, the Republic of Kazakhstan has concentrated significant volumes of obsolete, non-utilized pesticides that are stored in dilapidated warehouses, polluting the surrounding area. To study the mutagenic effects of pesticides on mouse rodents in 2018-19. territories near five former storage sites of obsolete and banned pesticides were examined, near farmland areas where pesticides were used in the past and control territory. The mouse indicators were bioindicators. Indicators of the main metric and functional parameters of indicator animals indicate that no abnormalities have been identified, and they generally correspond to similar characteristics of these animal species living in Kazakhstan in non-polluted territories. Nevertheless, an assessment of the genetic status of mouse-like rodents captured at the monitoring points of Belbulak, Amangeldy, Kyzylkairat, Enbekshi, near the storage sites of old unused pesticides, indicates a significant increase in the frequency of violations of the genetic apparatus of the animals studied. A correlation analysis of the results of assessing the degree of DNA damage in monitoring animals by the comet-test method and the total POP content in the soil of the studied territories revealed a quantitative estimate of the bond tightness of 0.70 units, which on the Cheddock scale characterizes the qualitative strength of the bond as “noticeable / high” and is satisfactorily described corresponding polynomial equation. A statistically significant relationship was found both between the test systems used on mouse rodents and the frequency of chromosomal aberrations when analyzing the mutagenicity of soil samples from the studied villages on human lymphocyte cultures. Key words: bioindication, micronuclei, mouse-like rodents, pesticides, comet-test.